Successful Allogeneic Hematopoietic Stem Cell Transplantation of a Patient Suffering from Type II Congenital Dyserythropoietic Anemia A Rare Case Report from Western India - Gaurang Modi; Sandip Shah; Irappa Madabhavi; Harsha Panchal; Apurva Patel; Urmila Uparkar; Asha Anand; Sonia Parikh; Kinnari Patel; Kamlesh Shah; Swaroop Revannasiddaiah (Case Reports in Hematology, 2015)
The most frequent form of congenital dyserythropoiesis (CDA) is congenital dyserythropoietic anemia II (CDA II). CDA II is a rare genetic anemia in humans, inherited in an autosomally recessive mode, characterized by hepatosplenomegaly normocytic anemia and hemolytic jaundice. Patients are usually transfusion-independent except in severe type. We are here reporting a case of severe transfusion-dependent type II congenital dyserythropoietic anemia in a 5-year-old patient who has undergone allogeneic hematopoietic stem cell transplantation (HSCT) at our bone marrow transplantation centre. Patient has had up until now more than 14 mL/kg/month of packed cell volume (PCV), which he required every 15 to 20 days to maintain his hemoglobin of 10 gm/dL and hematocrit of 30%. His pre-HSCT serum ferritin was 1500 ng/mL and he was on iron chelating therapy. Donor was HLA identical sibling (younger brother). The preparative regimen used was busulfan, cyclophosphamide, and antithymocyte globulin (Thymoglobulin). Cyclosporine and short-term methotrexate were used for graft versus host disease (GVHD) prophylaxis. Engraftment of donor cells was quick and the posttransplant course was uneventful. The patient is presently alive and doing well and he has been transfusion-independent for the past 33 months after HSCT.